Green-synthesized silver nanoparticles kill virulent multidrug-resistant Pseudomonas aeruginosa strains: A mechanistic study - Balaram Das; Sandeep Kumar Dash; Debasis Mandal; Jaydeep Adhikary; Sourav Chattopadhyay; Satyajit Tripathy; Aditi Dey; Subhankar Manna; Sankar Kumar Dey; Debasis Das; Somenath Roy (Wolters Kluwer Medknow Publications, 2016)
Background: Due to abuse and improper prescribing policy of antibiotics, the antibiotics resistance were remarkably increased in Pseudomonas aeruginosa, so there are urgently need to develop a new kind of antimicrobial to treat Pseudomonas aeruginosa infection. Biosynthesized silver nanoparticles (Ag NPs) have showed its interesting impact against bacterial infection drawn researchers to green nanotechnology. Aims: The study was conducted to evaluate the antibacterial activity of AgNPs against multi drug resistant P. aeruginosa isolated from urine sample of UTI patients. Methods: 126 UTI patent's urine samples were included in the study. P. aeruginosa strains were isolated, identify, antimicrobial susceptibility, drug resistance mechanisms were done as per routine laboratory protocol. The antimicrobial activity and mechanisms of the killing of Ag NPs were studied. Results: From this study, it was revealed that 25 (19.84%) isolates were multi drug resistant Pseudomonas aeruginosa. Green synthesized Ag NPs successfully destroyed the multi drug resistant strains via ROS generation and membrane damage. The prevalence of multidrug resistance is increased worldwide and there are urgently need another option to control the multidrug resistant strains. Conclusion: The findings of the study suggested that Ag NPs might be used to treat the multi drug resistant Pseudomonas aeruginosa.